Development of measuring tools for muscle strength and endurance arm for archery sport holding bow digitec test - Prasetyo, Heru; Siswantoyo; Prasetyo, Yudik; Wali, Carles Nyoman (Journal Sport Area, 2022)
This study aims to produce a measuring instrument for arm muscle strength and endurance for “Archery Holding Bow Digitec Test”. It creates a new breakthrough that the “Holding Bow Digitec Test” is a tool for measuring arm muscle strength and endurance with high validity and reliability for archery. This research is a type of research and development (R&D) research that uses the Borg & Gall development model which consists of 10 procedures. The subjects involved in this study amount to 33 subjects consisting of 18 male archers and 15 female archers. Data collection techniques use questionnaires, the delphi method, and measurement tests. Data analysis uses the percentage formula for the questionnaire. The validity test uses content validity which is analyzed using the Aiken's v formula and concurrent validity which is analyzed using product moment correlation. The reliability test used a test-retest approach which is analyzed using product moment correlation. The results of the study are a tool for measuring the strength and endurance of the arm muscles in archery called the “Holding Bow Digitec Test”. The contribution of this research is to present a practical archery tool to measure arm strength and muscle power of adult archery athletes. It is the hope of the researcher that this research is continued with a large range of benefits in terms of subject, place and benefits, not only in one category but the tools developed can be used by categories of children and adolescents.